The Changes and Innovation of Radio Media in the Digital Era - Mohammad Ismed (2020)
The Changes and Innovation of Radio Media in the Digital Era. This study aims at analyzing the changes made by radio in the digital era in radio's customers compared to what happened in the past. Both changes in business and radio innovation are also discussed. With qualitative approach and descriptive interview and observation methods, this study concluded that the development of digital technology has changed the way of listeners towards the radio. Additionally. the lifestyle and the channels usages also changed. For this reason, radio innovates with what is called Tri-O, the integration of the concept of program presentation and ad placement in terms of On Air, Off Air and also Online as a result of the evolutionary process carried out by the radio itself. With all the innovations made by radio media, the fact that radio is no longer just audio can also be added to the visual aspect.